Fasudil, a clinically safe ROCK inhibitor, decreases disease burden in a Cbl/Cbl-b deficiency-driven murine model of myeloproliferative disorders. Issue 4 (20th April 2016) - William, Basem M.; An, Wei; Feng, Dan; Nadeau, Scott; Mohapatra, Bhopal C.; Storck, Matthew A.; Band, Vimla; Band, Hamid
Abstract : Objectives : Mutations in Cbl or Cbl-b gene occur in 10% of myeloproliferative disorder (MPD) patients and are associated with poor prognosis. Hematopoietic Cbl/Cbl-b double knockout (DKO) leads to a disease in mice phenotypically similar to human MPDs. The aim of this study was to evaluate the anti-MPD activity of a clinically safe drug, Fasudil, identified in an in vitro kinase inhibitor as an inhibitor of proliferation of DKO mouse hematopoietic stem/progenitor cells (HSPCs). Methods : Fasudil exhibited relatively selective anti-proliferative activity against Cbl/Cbl-b DKO vs. control murine bone marrow HSPCs. We established a mouse model with uniform time of MPD onset by transplanting Cbl/Cbl-b DKO HSPCs into busulfan-conditioned NOD/SCID/gamma chain-deficient mice. Four weeks post-transplant, mice were treated with 100 mg/kg fasudil (13 mice) or water (control, 8 mice) daily by oral gavage, followed by blood cell count every 2 weeks. Results : By 2 weeks of treatment, total white cell and monocyte counts were significantly lower in mice treated with fasudil. We observed a trend towards improved survival in fasudil-treated mice that did not reach statistical significance. Notably, prolonged survival beyond 27 weeks was observed in two fasudil-treated mice, nearly twice the 16-week average life-span in the Cbl/Cbl-b DKO MPD model. Conclusions : Our results suggest a therapeutic potential for fasudil, a clinically safe drug with promising results in vascular diseases, in the treatment of MPDs or other mutant Cbl-driven myeloid disorders.